Classifying alcohol control policies enacted between 2000 and 2020 in Poland and the Baltic countries to model potential impact. (26th December 2022) - Rehm, Jürgen; Lange, Shannon; Gobiņa, Inese; Janik‐Koncewicz, Kinga; Miščikienė, Laura; Reile, Rainer; Stoppel, Relika; Tran, Alexander; Ferreira‐Borges, Carina; Jasilionis, Domantas; Jiang, Huan; Kim, Kawon Victoria; et al.
Abstract: Aims: The study's aim is to identify and classify the most important alcohol control policies in the Baltic countries (Estonia, Latvia and Lithuania) and Poland between 2000 and 2020. Methods: Policy analysis of Baltic countries and Poland, predicting potential policy impact on alcohol consumption, all‐cause mortality and alcohol‐attributable hospitalizations was discussed. Results: All Baltic countries implemented stringent availability restrictions on off‐premises trading hours and different degrees of taxation increases to reduce the affordability of alcoholic beverages, as well as various degrees of bans on alcohol marketing. In contrast, Poland implemented few excise taxation increases or availability restrictions and, in fact, reduced stipulations on prior marketing bans. Conclusions: This classification of alcohol control policies in the Baltic countries and Poland provides a basis for future modeling of the impact of implementing effective alcohol control policies (Baltic countries), as well as the effects of loosening such policies (Poland).